ChemInform Abstract: Chiral Pyridinium Phosphoramide as a Dual Broensted Acid Catalyst for Enantioselective Diels—Alder Reaction. Issue 38 (September 2016) - Nishikawa, Yasuhiro; Nakano, Saki; Tahira, Yuu; Terazawa, Kanako; Yamazaki, Ken; Kitamura, Chitoshi; Hara, Osamu
Abstract: The title catalysts are applied in the highly enantioselective Diels—Alder reaction between 1‐amino dienes with maleimides or benzoquinones.